KESEJAHTERAAN MASYARAKAT DENGAN ADANYA BUMDES SUMBER REZEKI DESA RANTAU SAKTI - Paidi (Jurnal Ilmiah Cano Ekonomos, 2023)
The approach that is expected to encourage and drive the wheels of the rural economy is the establishment of economic institutions that are fully managed by the village community. This economic institution is no longer established according to government instructions but the wishes of the village community, starting from managing the potential to generate market demand. It is necessary to hold BUMDes as a support for community welfare in both economic and social aspects. The purpose of this study was to determine the welfare of the community with the Sumber Rejeki BUMDes of Rantau Sakti Village in terms of economic and social aspects. The research method used is qualitative research using data collection techniques of observation, interviews and documentation studies. The data analysis technique uses the validation of the three data collection techniques and draws conclusions. The results of the study show that the community with the Sumber Rejeki Village BUMDes Rantau Sakti is classified as prosperous in terms of economic and social aspects including managing clean water and facilitating electricity payments.